2017
DOI: 10.1002/jgt.22213
|View full text |Cite
|
Sign up to set email alerts
|

On the possible values of the entropy of undirected graphs

Abstract: The entropy of a digraph is a fundamental measure which relates network coding, information theory, and fixed points of finite dynamical systems. In this paper, we focus on the entropy of undirected graphs. We prove that for any integer k the number of possible values of the entropy of an undirected graph up to k is finite. We also determine all the possible values for the entropy of an undirected graph up to the value of four.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Let F be a graph in F 1 . By [9], the values of the asymptotic guessing number of graphs can be enumerated as (a i : i ∈ N) where a i < a i+1 for all i ∈ N. We have a 0 = 0, a 1 = 1, a 2 = 2, a 3 = 2.5, . .…”
Section: Guessing Number and Forbidden Subgraphsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let F be a graph in F 1 . By [9], the values of the asymptotic guessing number of graphs can be enumerated as (a i : i ∈ N) where a i < a i+1 for all i ∈ N. We have a 0 = 0, a 1 = 1, a 2 = 2, a 3 = 2.5, . .…”
Section: Guessing Number and Forbidden Subgraphsmentioning
confidence: 99%
“…Let A be a maximum independent set in F and B = V (F ) \ A. By Lemma 3.2 of [9], there exists a nonempty Corollary 34. For any a > 0 there exists a unique finite family of minimal forbidden subgraphs F a such that, for any graph G, gn(G) < a ⇔ G is F a -free.…”
Section: Guessing Number and Forbidden Subgraphsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also related to the problem of index coding with side information [2,10]. Gadouleau showed that this problem can also be recast in terms of fixed points of finite dynamical systems [9]. Christofides and Markström were the first to expand the study of guessing numbers of undirected graphs [6].…”
Section: Introductionmentioning
confidence: 99%